Wlan Network’s Design For The Colombian Red Cross Barrancabermeja’s Head Office - Aldana Charry, Lorena Juliet; Dávila Ávilez, Iludina María; Ruíz Toro, Javier Antonio (Ingeniería Solidaria, 2010)
The objective of this article is to present the design of a Wireless Local Area Network (WLAN) for the Colombian Red Cross, head office Barrancabermeja. In the initial phase the current state of the institution and the study for the implementation of the WLAN are shown; in the phase of analysis the possible solutions to improve the services given to the community are determined; in the phase of design the standards and the topology that must be implemented are described; the form in which the WLAN can be created having in mind the devices, the wired up ones and the safety to administer the network are also detailed. Finally, in the phase of execution, the results appear with an evidence of the project and the functionality of the network: logical and physical map, the same as the packet tracer V.5.0. simulation.